AASHTO guide specifications for LRFD seismic bridge design (American Association of State Highway and Transportation Officials, 2023)
"These guide specifications have been developed for use in the design and construction of conventional bridges to resist the effects of earthquake motions. They have been approved as an alternative to the seismic provisions in the AASHTO LRFD Bridge Design Specifications, 9th Edition, and differ from those provisions in the use of displacement-based design procedures, rather than the traditional force-based R-Factor method. The guide specifications contain detailed guidance and commentary on earthquake-resisting elements and systems, global design strategies, demand modeling, capacity calculation, and liquefaction effects. Capacity design procedures underpin the guide specifications' methodology and include prescriptive detailing for plastic-hinging regions and design requirements for capacity protection of those elements that should not experience damage." -- Publisher's website.